Comprehensive geriatric assessments in integrated care programs for older people living at home: A scoping review. (21st June 2019) - Stoop, Annerieke; Lette, Manon; van Gils, Paul F.; Nijpels, Giel; Baan, Caroline A.; de Bruin, Simone R.
Abstract: In many integrated care programs, a comprehensive geriatric assessment (CGA) is conducted to identify older people's problems and care needs. Different ways for conducting a CGA are in place. However, it is still unclear which CGA instruments and procedures for conducting them are used in integrated care programs, and what distinguishes them from each other. Furthermore, it is yet unknown how and to what extent CGAs, as a component of integrated care programs, actually reflect the main principles of integrated care, being comprehensiveness, multidisciplinarity and person‐centredness. Therefore, the objectives of this study were to: (a) describe and compare different CGA instruments and procedures conducted within integrated care programs for older people living at home, and (b) describe how the principles of integrated care were applied in these CGAs. A scoping review of the scientific literature on CGAs in the context of integrated care was conducted for the period 2006–2018. Data were extracted on main characteristics of the identified CGA instruments and procedures, and on how principles of integrated care were applied in these CGAs. Twenty‐seven integrated care programs were included in this study, of which most were implemented in the Netherlands and the United States. Twenty‐one different CGAs were identified, of which the EASYcare instrument, RAI‐HC/RAI‐CHA and GRACE tool were used in multiple programs. The majority of CGAs seemed to reflect comprehensiveness, multidisciplinarity and person‐centredness, although the way and extent to which principles of integrated care were incorporated differed between the CGAs. This study highlights the high variability of CGA instruments and procedures used in integrated care programs. This overview of available CGAs and their characteristics may promote (inter‐)national exchange of CGAs, which could enable researchers and professionals in choosing from the wide range of existing CGAs, thereby preventing them from unnecessarily reinventing the wheel.